The Students’ Perceptions of Using Multimodal Podcasts in Enhancing Listening Skill - Winda Aulia; Diah Safithri Armin (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2026)
The purpose of this study was to determine students' perceptions of using multimodal podcasts in enhancing listening skill. The problem in this research is many students have below average listening abilities due to a lack of listening practice and a lack of knowledge of listening learning media. This study employed a descriptive qualitative method. It employed observation and semi structured interviews as the instruments. Participants were 5 students second-grade senior high school students at a public high school in Asahan Regency. 1 student as key-informant and 4 student as supporting informant.The result of this research was found that the multimodal podcasts is really helps students improve their listening skills.The study's results found five student perceptions of using the multimodal podcasts. The five perceptions include the ease of use of the application (usability), effectiveness in improving understanding of English listening (effectiveness), available controllable features and quizzes (interactivity), increasing students' motivation when learning English listening (motivation) and students are satisfied with their learning listening experience using multimodal podcasts (satisfaction).Most participants preferred the Learn English Video app as a medium for learning English listening.